Numerical study of the effect of operation parameters on particle segregation in a coal beneficiation fluidized bed by a TFM–DEM hybrid model. (28th July 2015) - Wang, Qinggong; Yang, Hairui; Feng, Yuqing; Witt, Peter J.; Lu, Junfu; Yin, Weidi; Liu, Qing; Wei, Lubin
Abstract: A TFM–DEM hybrid model is introduced for modeling of the complex gas–solid flows in a pilot scale Coal Beneficiation Fluidized Bed (CBFB). The gas and the dense solid phases are modeled using an Eulerian-Eulerian or two fluid model (TFM), while the beneficiated coal particles are modeled as a dilute phase by the discrete element method (DEM). In this work, the influence of some key operation parameters on particle segregation behavior is studied, including fluidized air velocity, bed depth, and coal feed ratio and bed medium properties. Their effects are evaluated using a single coal sample of diameter 4.3 mm. Particles are divided into five different density fractions to represent the wide density range of raw coal samples. The simulation results demonstrate that by increasing the fluidizing air velocity from 1.2 u mf to 1.8 u mf of the dense medium solids, the segregation degree of beneficiated coal particles is significantly reduced, but the segregation time is only slightly decreased. Increasing the particle feed mass or decreasing the bed depth has a similar influence on CBFB operation. Both help to improve particle segregation, but a shallower bed is demonstrated to be more effective for coal beneficiation. A decrease in the medium density can reduce the bed cut density as well as the beneficiation limit for lighter samples, while a decrease in the medium size will increase the back-mixing effects, resulting in reduced beneficiation quality. Hydrodynamic forces acting on the beneficiated particles are also quantified from the simulation results. By analyzing the magnitude and direction of each force acting on discrete particles, the mechanisms influencing particle segregation under different operation conditions are explained at the particle scale. Graphical abstract: Highlights: A TFM–DEM hybrid model is introduced to describe the multiphase flow in a CBFB. The fluidized carrier phases are modeled by a TFM while coal particles by a DEM. Effects of operation parameters on particle segregation are systematically studied. Hydrodynamic forces acting on the beneficiated particles are quantified in the results. The mechanisms influencing particles are explained at the particle scale.